Estudo das soluções empregadas em consolos curtos monolíticos de pilares pré-moldados na região de Pato Branco – PR - Luizetto, Eduardo Cezar (2014)
This research shows a market study that treats the implementation of console-pillar connections in structures of precast concrete in the Pato Branco region, by the monitoring of the implementation at companies. The analysis is performed by discussions of solutions raised about the executive method applied, the positioning of the reinforcement of the element and the accordance with the existing standards governing the subject. Based on this analysis, it was found that the methods used vary too much and the recommendations of the standard are not obeyed in 100% of the studied sample, the reason given is the incompatibility between equipment provided and the correct execution form, according to the standards, another aspect found is the persistence of empiricism in such methods.